Great lakes, fragile seas [videorecording] - Seamans, Joe (The Society, 1991)
North America's freshwater seas have been subjected to decades of human abuse. Documents concurred groups attempting to repair past damage and confronting new threats to these waters. Shows how bodies of water affect lives of people. Shows the multifaceted aspects of the seas and other bodies of water. It discusses the beauty and magnificance of the bodies of waters as well as their harmful effects of man's abuse of our water resources.